Milled flaxseed-added diets ameliorated hepatic inflammation by reducing gene expression of TLR4/NF-κB pathway and altered gut microbiota in STZ-induced type 1 diabetic mice - Hui Xia; Xiangling Shi; Beijia Zhou; Jing Sui; Chao Yang; Hechun Liu; Ligang Yang; Shaokang Wang; Guiju Sun (Food Science and Human Wellness)
Flaxseed has displayed the potential beneficial as functional foods. However, most studies focused on effects of flaxseed extracts or ingredients in flaxseed. Besides, few studies showed that flaxseed extracts contributed to anti-type 1 diabetes (T1D), yet the underlying mechanism is still unknown. In the present study, 16.7% of milled flaxseed (MF)-added diet was given to diabetic mice induced by streptozocin for 6 weeks. The results showed that MF feeding 1) slightly decreased blood glucose levels and improved the ability of glucose tolerance by oral glucose tolerance test, 2) decreased liver tumor necrosis factor-α levels and increased liver glycogen levels with significance via down-regulating TLR4/NF-κB pathways, 3) and significantly altered some beneficial bacteria in gut microbiota. In conclusion, the present study showed that milled flaxseed showed the potential on anti-T1D through anti-inflammation via TLR4/NF-κB and altering the gut microbiota in STZ-induced diabetic mice.